The Many Faces of Deprivation : A Multidimensional Approach to Poverty in Armenia - Martirosova, Diana; Inan, Osman Kaan; Meyer, Moritz; Sinha, Nistha (World Bank, Washington, DC, 2017)
This note describes a new measure of multidimensional poverty developed for Armenia. In 2013, the National Statistical Service of the Republic of Armenia and the World Bank began work on a national measure of multidimensional poverty to supplement the consumption poverty indicator. This measure, which was identified through consultations with many stakeholders in Armenia, reflects deprivations specific to Armenia in the areas of education, health, labor, housing conditions, and basic needs. The approach offers insights into the complexity, depth, and persistence of poverty in the country; tailoring it specifically to the country context enhances its relevance for policy. This note uses the new measure to describe national trends and regional patterns.